Assessment of sorption-enhanced crude glycerol steam reforming process via CFD simulation. (9th August 2018) - Wang, Shuai; Yang, Xuesong; Xu, Shaodong; Zhang, Kai; Li, Bowen
Abstract: The sorption-enhanced glycerol reforming performance in a fluidized bed reactor is numerically studied with CaO and Li4 SiO4 as CO2 sorbents, where the multi-fluid model with the kinetic theory of granular flow is employed to carry out three-dimensional simulations. The ethanol is treated as the impurity in the crude glycerol and its effect on the reforming performance is evaluated. It is found that the hydrogen yield is higher using the crude glycerol with the ethanol owing to a greater reaction rate of the ethanol. An increase of the temperature is beneficial to the glycerol conversion and hydrogen production. Meanwhile, the enhancing effect on the reforming performance of CaO and Li4 SiO4 is compared. The result demonstrates that the enhancing reforming effect of the Li4 SiO4 -based sorbent is similar to that of the CaO-based sorbent. At a high temperature, the CaO-based sorbent has a better performance. Highlights: Sorption enhanced crude glycerol steam reforming process is simulated. The capacity of Li-based sorbent and impurities effect is examined. Dependence of sorption process on temperatures is discussed.